2012
DOI: 10.2478/v10045-012-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Three Entomopathogenic Fungi Alone or in Combination With Diatomaceous Earth Modifications for the Control of Three Pyralid Moths in Stored Grains

Abstract: The efficacy of Natural diatomaceous (DE) alone and combined with three fungal pathogens: Beauveria bassiana, Metarhizium anisopliae and Isaria fumosorosea against three moth species, Plodia interpunctella, Ephestia cautella and E. kuehniella was evaluated. Modified diatoms with Calcium hydroxide (Ca-DE) and modified diatoms with Sodium hydroxide (Na-DE) were the highlight treatments against tested insects and achieved the highest mortality percentages. E. kuehniella achieved the highest tolerant to tested DEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
4
20
0
2
Order By: Relevance
“…This result approved the finding of Sabbour et al [13], however, the LC 50 of fungus in their study was 1.29 × 10 9 con. mg −1 which was much greater than that of our finding, 1 × 10 5 con.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result approved the finding of Sabbour et al [13], however, the LC 50 of fungus in their study was 1.29 × 10 9 con. mg −1 which was much greater than that of our finding, 1 × 10 5 con.…”
Section: Discussionsupporting
confidence: 92%
“…Some reports have pointed out to the promising control effects of B. bassiana on Indian meal moth [12] [13]. However the fungi encountered some limiting factors to show adequate level of pest control.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Wakil et al found that B. bassiana combined with DE or the neonicotinoid insecticide thiamethoxam increased the mortality of R. dominica adults, compared with individual treatments, and a significant additive effect was observed [32]. Similar synergistic interactions were observed when the tested fungi B. bassiana, M. anisopliae, and I. fumosorosea were combined with DE against Plodia interpunctella, Ephestia cautella, and Ephestia kuehniella [51]. Therefore, it is important to understand how a pathogen interacts with other insecticides and adjuvants.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, combining fungal biocontrol agents with adjuvants and Insects 2020, 11,93 3 of 20 other insecticides with good compatibility is an effective and reliable solution to improve the pest control effect [15,18,32,39,48]. Numerous studies have reported that the combination of EPF with insecticides [44,[48][49][50], DE [34,39,51,52], and with insecticides and DE have significantly improved their pest control efficacies [15,32,33,35]. For example, Nian et al [49] demonstrated that combining I. fumosorosea with sub-lethal doses of the insecticides beta-cypermethrin and bacillus thuringiensis caused synergistic effects against Plutella xylostella larvae under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Diatomaceous earths are naturally occurring siliceous sedimentary mineral compound formed from the fossils of tiny phytoplanktons (diatoms) which absorb the epicuticular lipids of the insect cuticle, causing death Corresponding author: Baba Gana Jugudum Kabir, Dr., Ph.D., research field: stored products entomology. through desiccation [9]. They are known to protect commodities against stored-product pests in two ways.…”
mentioning
confidence: 99%